2019
DOI: 10.4028/www.scientific.net/msf.944.473
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Antimicrobial Properties of Cu/TiB<sub>2</sub> Composite Coating on 304 Steel Surface Prepared by Laser Cladding

Abstract: In this study, Cu/TiB2 composite coating was in-situ prepared on 304 steel by laser cladding. This coating applies to hospitals, schools and some public places where cross infections happen more easily because of its good antimicrobial properties and abrasion resistance. Before laser cladding, pre-blend of Cu powder, Ti powder and B powder were undertaken by ball-milling in two different proportions (10% wt (Ti+B) and 20% wt (Ti+B)). And the atomic ratio of Ti and B was 1:2. After a series of experiments, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Cu 2+ ions kill microbial bacteria by breaking the cell membrane thereby killing bacteria, hence Cu has antibacterial properties [Oulmaset al, 2019]. Dense TiB2 coatings were corrosion-resistant in the corrosive medium [Sun, et al, 2019].TiB2-Ni coatings have been deposited using the HVOF (high-velocity oxy-fuel) process and their bonding and adhesion have shown significant improvement to the substrate [Senthil Kumar, and Murali Krishna, 2020;Gyawali, et al ., 2017]. Ti coatings have been found to increase the mechanical properties of substrate metal manifolds [Banday and Wani., 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2+ ions kill microbial bacteria by breaking the cell membrane thereby killing bacteria, hence Cu has antibacterial properties [Oulmaset al, 2019]. Dense TiB2 coatings were corrosion-resistant in the corrosive medium [Sun, et al, 2019].TiB2-Ni coatings have been deposited using the HVOF (high-velocity oxy-fuel) process and their bonding and adhesion have shown significant improvement to the substrate [Senthil Kumar, and Murali Krishna, 2020;Gyawali, et al ., 2017]. Ti coatings have been found to increase the mechanical properties of substrate metal manifolds [Banday and Wani., 2020].…”
Section: Introductionmentioning
confidence: 99%
“…However, such research is limited to a low amount of TiB 2 in the Ag matrix, and the antimicrobial effect of such composite is not examined. Sun et al reported a laser-cladding prepared Cu/TiB 2 composite with a hardness of 70 HRC and excellent abrasion resistance, although at the expense of decreasing the antibacterial effect after adding TiB 2 [26].…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2+ ions kill microbial bacteria by breaking the cell membrane thereby killing bacteria, hence Cu has antibacterial properties [14]. Dense TiB2 coatings were corrosion-resistant in the corrosive medium [15].TiB2-Ni coatings have been deposited using the HVOF (high-velocity oxy-fuel) process and their bonding and adhesion have shown significant improvement than the substrate [16,17].…”
Section: Introductionmentioning
confidence: 99%